2021
DOI: 10.1590/1678-4162-12079
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical ketosis risk prediction in dairy cows based on prepartum metabolic indices

Abstract: Ketosis can seriously impair cow performance. This study detected changes in prepartum blood metabolic parameters for predicting postpartum ketosis occurrence in dairy cows. Body condition score (BCS) was assessed before and after delivery. Blood samples of 63 cows were collected from 10 days before calving to 10 days after calving to measure metabolic parameters including β-hydroxybutyric acid (BHBA), non-esterified fatty acid (NEFA), glucose (GLU), total bilirubin (TBIL), direct bilirubin (DBIL), indirect bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The results of this study showed that energy-related indices such as NEFA, BHB, glucose, insulin, and RQUICKI may not predict postpartum ketosis in primiparous cows. Because of the differences in parity, these results do not apply to previous potential warning techniques based on NEFA, BHB, and glucose ( Wang et al, 2021 ). Therefore, potential warning biomarkers of ketosis were identified in primiparous cows using metabolomic and microbiological approaches.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The results of this study showed that energy-related indices such as NEFA, BHB, glucose, insulin, and RQUICKI may not predict postpartum ketosis in primiparous cows. Because of the differences in parity, these results do not apply to previous potential warning techniques based on NEFA, BHB, and glucose ( Wang et al, 2021 ). Therefore, potential warning biomarkers of ketosis were identified in primiparous cows using metabolomic and microbiological approaches.…”
Section: Discussionmentioning
confidence: 70%
“…Because of the differences in parity, these results do not apply to previous potential warning techniques based on NEFA, BHB, and glucose (Wang et al, 2021). Therefore, potential warning biomarkers of ketosis were identified in primiparous cows using metabolomic and microbiological approaches.…”
Section: Discussionmentioning
confidence: 91%
“…BHB levels in the blood of heifers ranged from 0.43 to 0.59 mmol/L 5-7 days before calving. According to Wang et al (2021), exceeding the level of 0.43 mmol/L for BHB and 0.27 mmol/L for NEFA before calving indicates a high risk of developing subclinical ketosis in the postpartum period. In our study, 20% of heifers had BHB levels above 1.0 mmol/L within 2-3 days after calving, and this number increased to 40% within 7-10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers indicate that during the prepartum period, there are various changes in blood parameters, particularly, AST activity and NEFA levels, which can be used as risk indicators for predicting the occurrence of subclinical ketosis in cows after calving (Wang et al, 2021). Biochemical markers one week after calving had high prognostic value for the development of displaced abomasum (with BHB concentration above 1000 µmol/L, the odds were 13.6 times higher) and for the development of clinical ketosis (with serum NEFA above 1.0 mmol/L the odds were 6.3 times higher, and 4.7 times higher with BHB concentration above 1200 µmol/L) (Seifi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increased lipomobilization and ketogenesis lead to fatty liver syndrome (decrease in cholesterol and triglyceride levels in the blood), along with hepatocyte necrosis syndrome [increased activity of the liver enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT)], biliary retention syndrome (increased total bilirubin) decreased hepatocyte secretion syndrome (decreased albumin value), and insulin resistance (Delić et al, 2020). Recent results have shown that these and many other parameters deviate in their values during ketosis in cows (Wang, 2021;Dervishi et al, 2021) The aim of this study is to examine the interrelationships and significance of blood parameters in the assessment of BHB values in healthy and ketotic cows using multiparameter statistics.…”
Section: Introductionmentioning
confidence: 99%